Sítě s volnou typologií se zaměřením na technologii MANET - Sehnálek, Adam (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2008)
Hlavním předmětem mé bakalářské práce je seznámení se s problematikou počítačových sítí s volnou topologií se zaměřením na technologii MANET, resp. Motorola MESH. Zabývá se simulací vlivu počtů uzlů v sítí na přenos dat pomocí veškerých dostupných směrovacích protokolů v Opnet Modeler. V první části popisuje základní sítě s volnou topologií a popisuje jejich vlastnosti. Převážně se věnuje sítím typu Mesh a nejvíce technologii od firmy Motorola. Veškeré použité technologie firmy Motorola jsou zde popsány. Naleznete zde uvedeny všechny tři druhy sítí Motorola, a to MOTOMESH Solo, MOTOMESH Duo a MOTOMESH Quattro. Druhá část práce se zaměřuje na směrovací protokoly dostupné pro sítě MANET v Opnet Modeler. Jsou zde popsány principy a základní vlastnosti protokolů AODV (Ad-hoc On-demand Distance Vector), DSR (Dynamic Source Routing), OLSR (Optimized Link State Routing protocol) a TORA/IMEP (Temporally-Ordered Routing Algorithm) a GRP (Geographic Routing Protocol). Závěrečná část bakalářské práce se zabývá simulací jednotlivých protokolů a jejich vlivu na přenos multimediálních dat přes síť. Je zde popsán přesný postup vytvoření sítě MANET, nastavení jednotlivých prvků, zvolení potřebných charakteristik a zobrazení po simulaci. Kapitola obsahuje i závěrečné shrnutí všech simulovaných protokolů.

The main goal of my bachelor thesis is familiarization with a question of computer network with free topology aimed at MANET technology, or more precisely Motorola MESH. It deals with simulation of influence of bundle number within the network on data transfer using all possible routing protocols in Opnet Modeler. The first part contains description of basic networks with free topology and their characteristics. It devotes mainly to Mesh networks and mostly to Motorola technologies that are described there. All three Motorola network types can be found there - MOTOMESH Solo, MOTOMESH Duo and MOTOMESH Quattro. The second part of the thesis focuses on routing protocols available for MANET networks in Opnet Modeler. Principles and basic characteristics of protocols AODV (Ad-hoc On-demand Distance Vector), DSR (Dynamic Source Routing), OLSR (Optimized Link State Routing protocol) and TORA/IMEP (Temporally-Ordered Routing Algorithm) a GRP (Geographic Routing Protocol) are described there. The closing part of the thesis is dedicated to the simulation of individual protocols and their influence on transferring multimedia data through the network. It includes exact process of making the MANET network, configuration of individual components, choosing the necessary characteristics and after simulation view. It concludes also the final summary of all simulated protocols.
Scale free topology networks focused on MANET technology
Keywords: MANET; MESH; AODV; DSR; OLSR; TORA; IMEP; GRP; Motorola; Opnet; Solo; Duo; Quattro; síť; simulace; MANET; MESH; AODV; DRS; OLSR; TORA; IMEP; GRP; Motorola; Opnet; Solo; Duo; Quattro; network; simulation